2010
DOI: 10.1183/09031936.00089610
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive algorithm to exclude pre-capillary pulmonary hypertension

Abstract: Current guidelines recommend right heart catheterisation (RHC) in symptomatic patients at risk of pre-capillary pulmonary hypertension (PH) with echocardiographic systolic pulmonary artery pressures o36 mmHg. Growing awareness for PH, a high prevalence of postcapillary PH and the inability to distinguish between pre-and post-capillary PH by echocardiography have led to unnecessary RHCs. The aim of our study was to assess whether standard noninvasive diagnostic procedures are able to safely exclude pre-capillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 51 publications
5
69
0
8
Order By: Relevance
“…Our model differs from the study by BONDERMAN et al [35], as we specifically aimed to identify LHF as alternative cause of PH, whereas the model of BONDERMAN et al [35] aimed to exclude PAH and included patients with normal pulmonary pressures. Considering this, and as logistic regression models have better predictive characteristics compared to regression trees, the model of BONDERMAN et al [35] and our own model may have additional value in reducing the need for RHC [36]. The LHF patient cohort in our study displays specific characteristics, with relatively elevated PVR and pulmonary artery pressures.…”
Section: Figurementioning
confidence: 64%
See 3 more Smart Citations
“…Our model differs from the study by BONDERMAN et al [35], as we specifically aimed to identify LHF as alternative cause of PH, whereas the model of BONDERMAN et al [35] aimed to exclude PAH and included patients with normal pulmonary pressures. Considering this, and as logistic regression models have better predictive characteristics compared to regression trees, the model of BONDERMAN et al [35] and our own model may have additional value in reducing the need for RHC [36]. The LHF patient cohort in our study displays specific characteristics, with relatively elevated PVR and pulmonary artery pressures.…”
Section: Figurementioning
confidence: 64%
“…BONDERMAN et al [35] showed that in the absence of right ventricular strain and, subsequently, an NT-proBNP level ⩽80 pg·mL , PAH can be excluded. Our model differs from the study by BONDERMAN et al [35], as we specifically aimed to identify LHF as alternative cause of PH, whereas the model of BONDERMAN et al [35] aimed to exclude PAH and included patients with normal pulmonary pressures.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…While the gold standard of CO determination is the direct Fick method, this method is rarely used in the clinical setting because of the technical and logistical demands involved in directly measuring V9O 2 , which makes this method impractical. As a result, the current reference standards most commonly employed in clinical practice in the evaluation of patients with PH, and the cardiac output methods employed in the largest PH registries, are the indirect Fick and TD methods, both of which are invasive and possess certain inherent limitations [2,14,15,17]. For example, TD suffers from imprecision because of the potential influences from catheter migration, differences in injector technique (with intra-and inter-investigator variability), the influence of the different phases of the respiratory cycle, and other factors [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%